Evaluation of ocean chlorophyll-a remote sensing algorithms using in situ fluorescence data in Southern Brazilian Coastal Waters (Ocean and Coastal Research, 2024)
A performance evaluation of ocean color chlorophyll-a algorithms was conducted based on the in situ fluorescencechlorophyll concentration (Fchl) measured by a sensor on the buoy SiMCosta-SC01 in coastal waters of South Brazil.The operational algorithms are used in MODIS and VIIRS sensors to derive satellite chlorophyll concentration (Csat). Fchlvalues were successfully corrected for nonphotochemical quenching (NPQ) by an interpolation of sunrise and sunsetdaily measurements. A laboratory-derived calibration coefficient was applied to convert the unquenching Fchl values intochlorophyll concentration (Cflu). Overall, linear regression analysis between Cflu and Csat for both sensors showed goodresults, with the coefficient of determination (R²) varying between 0.88 and 0.96, slopes between 0.92 and 1.02 andintercepts between -0.17 and 0.13. The MODIS algorithm (R² = 0.96, slope = 1.02, RMSE = 0.16 mg m-3, BIAS = 0.16 mg m-3,for N = 222 and time interval ±1 h) presented slightly better performance than VIIRS (R² = 0.92, slope = 0.96, RMSE = 0.25mg m-3, BIAS = -0.25 mg m-3, for N = 284 and time interval ±1 h). These results represent the most comprehensive satellitedata analysis for this region, suggesting that the approach may be applicable to other SiMCosta buoys